DevOps : automatic monitoring in public safety applications - Korhonen, Miiro (2021)
Nowadays, the software is being developed in a rapidly changing and unpredictable market. Technologies and tools have evolved fast, and companies are increasingly dependent on effective communication and information. The DevOps model has also been built on these needs. The DevOps model has its roots in software development models such as Agile and Lean thinking. Essential components in the DevOps model include automation and continuous practices.